Degree major, usage duration, and price as determinants of students' decision to buy, borrow, or ignore G.E. courses recommended reading titles - Razon, Ma. Sharon J., 1977-; Yang, Jackson V. (Quezon City Institute of Library Science, University of the Philippines Diliman, 2001)
In the competent world of tertiary education, it is the responsibility of college students to read in order to pass their courses. Reliable reading materials are those recommended by professors by which pointers are taken for class lectures, reports and examinations. With so many reading materials recommended to students, how do the students access the materials?
This study focus on the price, category and degree major as determinants in the decision of the students to buy or borrow the recommended reading materials, or ignore the professor's recommendation. The survey yielded 660 respondents, 652 (98.8 percent) of the respondents are evaluated. Chi-square was used for analysis proving the independence between degree majors, usage of category reading materials, price of reading materials and action taken on recommended reading materials.
Results show that degree major and action taken on recommended reading material for each course are independent except for mathematics 1 which proves the relationship of the two variables. Degree major and action taken on recommended reading materials in all G.E. courses are not independent. Prices and action taken on recommended reading materials are not independent. Usage category and action taken on recommended reading materials are also not independent.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: General education; Teaching -- Aids and devices